Pengaruh Bimbingan Kelompok Teknik Self Instruction Dalam Merubah Gaya Belajar Siswa - Muhammad An'im Dewantoro (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2022)
Abstract: The background of this research is that students do not know how to learn properly and correctly, students do not understand about learning styles and strategies that are suitable for them, students have not been able to find ways of learning that are suitable for learning styles, are difficult to understand lessons, and have not been able to utilize these learning resources. make learning outcomes less. The main problem studied is whether there is an effect of group guidance on self-instruction techniques in changing the learning styles of class XI science students at SMA N 1 Weleri.The research method used is true experimental with pretest-posttest control group design. The population in this study were all students of XI IPA SMA Negeri 1 Weleri totaling 144 students consisting of 4 classes. The sampling technique used is cluster random sampling technique. The analysis used to test the validity is product moment and reliability using the alpha formula. The final conclusion can be explained that the provision of treatment in the form of e-counseling services can be used to improve the ability of learning styles as evidenced by the implementation of treatment carried out for three meetings with the provision of treatment. Judging from the comparison of the results of the posttest calculations given to the experimental group, the e-counseling service had an average posttest score higher than the average posttest score for the control group without treatment, namely the score was 78.9 > 72.5. So it can be said that there is an influence of self-instruction technique group guidance in changing student learning styles in the experimental group than in the control group without any treatment. Suggestions that researchers can convey should be that the supervising teacher at the school provides advanced services regarding learning styles. Key Words: Self-instruction technique group guidance, learning style.